REVISITING STRATEGIC HUMAN CAPITAL FOR GREEN INNOVATION AND SUSTAINABILITY PERFORMANCE PUBLIC SECTOR: A SYSTEMATIC REVIEW AND INTEGRATED FRAMEWORK - Prilaksono, Kursusantyo Dudung; Setiyani , Aris; Sofiati , Nunung Ayu; Ali , M Mukti; Dayona, Gurawan (UJoST- Universal Journal of Science and Technology, 2026)
Phenomenon: As environmental, social, and governance (ESG) implementation, green transformation, and sustainability become more pressing worldwide, businesses are being urged to incorporate green innovation into their sustainability strategies. In this regard, strategic human capital has emerged as a crucial strategic skill that supports long-term competitive advantage and sustainability performance. However, prior research on the connection between sustainable performance, green innovation, and strategic human capital continues to show fragmented literature and conceptual inconsistencies, especially in the public sector where studies are still few. This study aims to develop an integrated framework that explains the interrelationships among Strategic Human Capital (SHC), Green Innovation (GI), and Sustainability Performance (SP) in public sector organizations through a systematic literature review. By synthesizing existing empirical and conceptual findings, the study provides a deeper understanding of the role of strategic human capital as a key driver of green innovation and sustainability performance, enabling public sector organizations to better respond to sustainable development imperatives and ESG implementation requirementsMethod: The Systematic Literature Review (SLR) method was used in this qualitative investigation. The Scopus database, Web of Science, and Science Direct was used for the article search process, and 186 articles were found at first. 32 final articles that satisfied the eligibility standards were examined after inclusion and exclusion criteria were applied. The chosen papers came from worldwide journals that were indexed in Scopus Q1 between 2020 and 2025. In order to discover prevailing theoretical viewpoints, mediation mechanisms, contextual elements, and research gaps in earlier studies, the analysis procedure comprised identification, screening, eligibility, inclusion, content analysis, and thematic synthesis. Results: The results show that through green innovation capabilities, crucial Human Capital plays a crucial role in improving sustainability performance. The main mediating mechanism between organizational sustainability results and human capital was found to be green innovation. Additionally, the study discovered that corporate sustainability transformation is highly influenced by organizational culture, digital transformation, ESG orientation, and innovation capabilities. Additionally, the results show that there are still comparatively few studies in the public sector compared to those in the private sector that look at the connection between sustainability performance, green innovation, and strategic human capital. The study highlights that strengthening strategic human capital through ESG-based civil servant training and green bureaucratic reform is crucial to accelerate green innovation amid public sector resource constraints Novelty: The establishment of an integrated framework that positions Strategic Human Capital as a strategic architecture linking green innovation, ESG orientation, organizational resilience, and sustainability performance concurrently is what makes this study distinctive